2021
DOI: 10.1111/bph.15366
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of prostaglandin‐endoperoxide synthase (PTGE) genes reveals genetic susceptibility for cross‐reactive hypersensitivity to NSAID

Abstract: Background and Purpose Cross‐reactive hypersensitivity to nonsteroidal anti‐inflammatory drugs (NSAIDs) is a relatively common adverse drug event caused by two or more chemically unrelated drugs and that is attributed to inhibition of the COX activity, particularly COX‐1. Several studies investigated variations in the genes coding for COX enzymes as potential risk factors. However, these studies only interrogated a few single nucleotide variations (SNVs), leaving untested most of the gene sequence. Experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The role of COX-1 inhibition in the etiopathogenesis of crosshypersensitivity to NSAIDs has been the object of controversy for years (Kowalski et al, 2007;Doña et al, 2018;Mastalerz et al, 2019). Supporting this hypothesis, it has been shown that COX-2 inhibitors are well tolerated among patients with crosshypersensitivity to NSAIDs (Morales et al, 2014;Bakhriansyah et al, 2019) and that patients with PTGS1 gene variants related to a decreased activity (Agúndez et al, 2014;Agúndez et al, 2015b;Lucena et al, 2019) are at increased risk of developing crosshypersensitivity to NSAIDs (García-Martín et al, 2021). Interestingly, preliminary evidence suggests that crosshypersensitivity to NSAIDs is dose-dependent (Palmer, 2005;Kong et al, 2007;Kowalski et al, 2013;Blumenthal et al, 2017) and, therefore, it could be speculated that individuals with impaired NSAID clearance (and therefore increased drug exposure) might have increased risk of developing cross-hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of COX-1 inhibition in the etiopathogenesis of crosshypersensitivity to NSAIDs has been the object of controversy for years (Kowalski et al, 2007;Doña et al, 2018;Mastalerz et al, 2019). Supporting this hypothesis, it has been shown that COX-2 inhibitors are well tolerated among patients with crosshypersensitivity to NSAIDs (Morales et al, 2014;Bakhriansyah et al, 2019) and that patients with PTGS1 gene variants related to a decreased activity (Agúndez et al, 2014;Agúndez et al, 2015b;Lucena et al, 2019) are at increased risk of developing crosshypersensitivity to NSAIDs (García-Martín et al, 2021). Interestingly, preliminary evidence suggests that crosshypersensitivity to NSAIDs is dose-dependent (Palmer, 2005;Kong et al, 2007;Kowalski et al, 2013;Blumenthal et al, 2017) and, therefore, it could be speculated that individuals with impaired NSAID clearance (and therefore increased drug exposure) might have increased risk of developing cross-hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on evaluating AA pathway-related variants or immune cell activation. 115,116 In NERD, variants in genes associated with LT production (5-Lipoxygenase, 5-LOX) and LTC4 synthase and PGs production (COX) pathways were reported. 115 Available data show that NECD and NIUA share similar genetic backgrounds; nevertheless, different gene polymorphisms have been reported.…”
Section: B I Omark Er S In N Saids Cross -Hyper Sen Sit Ivit Ymentioning
confidence: 99%
“…Genetic variants have been associated with NSAID hypersensitivity, being distinct in patients experiencing respiratory or cutaneous symptoms although most of them have not been replicated. Most studies have focused on evaluating AA pathway‐related variants or immune cell activation 115,116 . In NERD, variants in genes associated with LT production (5‐Lipoxygenase, 5‐LOX) and LTC4 synthase and PGs production (COX) pathways were reported 115 .…”
Section: Biomarkers In Nsaids Cross‐hypersensitivitymentioning
confidence: 99%
“…However, it shares with NSAIDs their antipyretic and analgesic properties as well as adverse drug events, such as hypersensitivity events in their two main clinical forms (selective hypersensitivity and cross-hypersensitivity) [ 4 , 5 , 6 , 7 ]. In addition, acetaminophen causes idiosyncratic drug-induced liver injury (iDILI) [ 8 , 9 , 10 ], as NSAIDs do, and it has been hypothesized that functional genetic variations in the COX-enzymes are related to iDILI risk and cross-hypersensitivity to COX-inhibitors [ 11 , 12 , 13 , 14 , 15 ], thus suggesting that patients with impaired COX activity are more prone to developing adverse drug events when using COX inhibitors [ 14 , 15 ]. Acetaminophen is also related to dose-dependent acute liver failure.…”
Section: Introductionmentioning
confidence: 99%